Desenvolvimento e avaliação de uma vacina inativada contra estirpe variante brasileira do vírus da bronquite infecciosa aviária - Santos, Romeu Moreira dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The infectious bronchitis (BIG) is an infectious disease caused by avian coronavirus (infectious bronchitis virus - IBV) that is widespread among commercial poultry flocks in the world. There are currently in Brazil, a predominance of infections caused by strains of IBV classified in variant genotype (BR-I), which reveal striking differences in antigenicity with regard to the vaccine strain Massachusetts, routinely used in this country. The consequence is a low cross-immunity and lower level of protection against Brazilian field isolates of genotype BR-I. Thus, the main objectives of this study were to formulate an experimental inactivated vaccine with a variant strain of IBV previously characterized as genotype BR-I and added of a new oil adjuvant and test it after an administration, at 1 day old, of a commercial attenuated Massachusetts vaccine, followed by the evaluation of humoral and cellular immune (CMI) responses, as well as the state of protection upon challenge with this variant strain of IBV by histopathological examination and absolute quantification of viral load present in the trachea, and kidneys of these birds vaccinated and challenged with this variant strain. The results of this study demonstrated that this immunoprophylactic approach (vaccination of birds with 1 day old with attenuated commercial vaccine and revaccination at 14 days of age with annual experimental inactivated vaccine) was able to elicit significant increases in the serum and tear levels of anti-IBV antibodies of IgG isotype, and also in the expression of CMI genes, especially of CD8  chain and Granzyme A in the vaccinated birds, which were associated with decreased histological lesions and reduced viral load in the trachea and kidney of vaccinated and challenged birds. It was concluded that humoral and cellular memory immune responses conferred by vaccination with this Brazilian variant strain of IBV combined to a previous Massachusets ...

A bronquite infecciosa das galinhas (BIG) é uma doença infecciosa causada pelo coronavírus aviário (vírus da bronquite infecciosa – VBI) que está amplamente disseminada entre as criações avícolas comerciais na maior parte do mundo. Há atualmente no Brasil, uma predominância de infecções causadas por estirpes do VBI classificadas no genótipo variante (BR-I), que revelam diferenças marcantes de antigenicidade com relação à estirpe vacinal Massachusetts, rotineiramente usada em nosso país. Isso resulta em uma baixa imunidade-cruzada e consequentemente em um menor nível de proteção contra isolados de campo do genótipo BR-I. Dessa forma, os objetivos principais do presente estudo foram formular uma vacina experimental inativada com, uma estirpe IBVPR-05 variante do genótipo BR-1 do VBI acrescida de um novo adjuvante oleoso; testá-la após a administração, com 1 dia de idade, da vacina comercial atenuada com estirpe Massachusetts, avaliando-se as respostas imunes humorais e cito-mediadas, bem como o estado de proteção ao desafio com essa estirpe variante do VBI através da avaliação histopatológica e quantificação absoluta da carga viral presente na traqueia e rins de aves vacinadas e desafiadas com a variante. Os resultados deste estudo demonstraram que esse esquema imunoprofilático (vacinação das aves com 1 dia de idade com vacina atenuada comercial e revacinação com 14 dias de idade com vacina inativada experimental homóloga) induziu aumentos significativos nos níveis de anticorpos lacrimais e séricos do isótipo IgG anti-VBI e também na expressão dos genes relacionados às respostas imunes cito-mediadas, sobretudo o da cadeia  do CD8 e da Granzima A, nas aves vacinadas, que se mostraram associados com a diminuição de lesões histológicas e uma menor carga viral na traqueia e rins nas aves vacinadas e desafiadas. Concluiu-se que as respostas imunes humoral e celular de memória conferidas ...
Keywords: Ave; Vacina veterinária; Bronquite infecciosa em ave domestica; Virus; Infecções por coronavírus; Veterinary vaccines